The Application of Business Judgment Rule Principles: The Protection for State-Owned Enterprises Directors to Business Risk Failure - Anita Kamilah; Trini Handayani (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
State-owned enterprises have a strategic position in realizing the mandate of the 4th paragraph of the Preamble of the 1945 Constitution. However, the absence of synchronization of laws and regulations in interpreting the  State-Owned Enterprises fund as separated state assets, creates legal uncertainty for the Board of Directors when losses arise due to business risks. This condition raises the issue of the board of directors' responsibilities in managing State-Owned Enterprise's finances. Thus, there is the need to apply the Principles of Business Judgment Rule in protecting the Directors from State-Owned Enterprises losses. The approach employed in this study was juridical normative research. Specifically, this study used descriptive analysis. The data were analyzed qualitatively. The findings revealed: (1) State-owned enterprises have played a role in realizing Indonesian Economic Democracy with their distinctive business characteristics, a profit-seeking company and social services provider to the community; (2) State-owned enterprise's losses are not related to state finances. This is because state equity participation has been transformed into state shares/funds to State-owned Enterprises whose management is based on the provisions of Limited Liability Companies; and (3) The principle of the Business Judgment Rule provides protection for the Board of Directors. It states that they can not be held accountable for the losses in state-owned Enterprises if the management of State Owned Enterprises is based on the following principles: (a) due of care; (b) due of skill; (c) good faith, and (d) for the best interest of the company. In conclusion, BUMN Persero that experiences losses due to business risks cannot be categorized as state financial losses. In addition, according to the principles of business judgment rule, Directors cannot be held accountable